Whatsapp for Mathematics Education Students’ Activeness in Learning English for Mathematics: A Case Study - Susanti Malasari; Paulina Besty Fortinasari (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
During the implementation of online learning in the new normal era, lecturers conducted the teaching and learning process by utilizing recent technology that could maximize the quality of the teaching and learning process. WhatsApp is one of the tools that is used as a teaching and learning medium in this new normal era. This is a case study that is aimed to explain whether the use of the WhatsApp application gave some effects on Mathematics Education students’ activeness in learning English for Mathematics. The participants of this research were the 4th semester Mathematics Education students’ who were studying English for Mathematics. The data from this study were obtained from observation and Focus Group Discussion. The findings revealed that the use of WhatsApp as an online learning medium affects students’ activeness in learning English for Mathematics in terms of speaking practice, students’ involvement, and students’ confidence.